Citizens’ perception of the role of urban nature-based solutions and green infrastructures towards climate change in Italy - Sturiale, Luisa; Scuderi, Alessandro; Timpanaro, Giuseppe (Frontiers in Environmental Science, 2023)
Climate change in recent years is shaping society's habits and life in large cities, then it will be necessary to plan and design nature-based urban solutions to meet different interests and needs. To enable this approach between cities, urban green spaces and climate change, sustainable and resilient urban growth models are needed, planned with the contribution of citizens as priority stakeholders. Citizens perceive and attribute value to Green Infrastructures (GIs), albeit in relation to different socio-economic and environmental variables, the assessment of which has only recently been addressed in specific research. This research analysed citizens' perceptions of GIs in combating the effects of the climate change. In particular, it revealed the degree of awareness of climate change, the value attributed to GIs and, finally, the willingness to pay to contribute to the maintenance of GIs in the city. The survey was carried out in the city of Catania (Italy), through the administration of questionnaires to a sample of residents (n=500). The results show that the citizens involved perceive GIs as strategic elements of the quality of urban life, although they are not always aware of their positive impact on climate change. Interest in the co-management of GIs was higher in the case of crowdfunding. An integrated two-step methodological scheme was applied (divided in two phases, univariate and multivariate statistical analysis), which proved effective in analysing the different needs perceived by citizens. This approach could become a useful tool for planning GIs, especially in the current context in which cities are facing challenges related to climate change and changing societal needs. Understanding citizens' views will be strategic in directing public investments towards GIs that can improve the quality of life in the urban ecosystem.